Cooperation and National Development - Ungku Abdul Aziz, Ungku Abdul Hamid (1966)
Every leader in the world opts for national development. National development does not merely involve economic development, but also other aspects that may interact with it, such as education, culture, health and armed forces. This paper mainly focuses on the definition of economic development and how cooperation can contribute towards national development. An introductory idea to economic development can be obtained by examining the objectives of a Government’s economic development plan. Generally, the First Malaysia Plan aims at increasing the income levels and consumption per head, especially those in the rural area, and to improve the general living standard as a whole. The economic expansion is different from economic development. The ideal economic development must include the elimination of poverty, unemployment as well as under-employment and inequality in the sharing of public services, such as health, education, water and electricity. The process of national economic development is well fit into the ideals of cooperation and with cooperative principles. How to increase the farmers’ or peasants’ income and the consumption power? The statistics show that private sectors in Malaysia still control in the economic markets, no matter in financing sectors, paddy milling sector or agricultural sector. The impact of cooperative movement is not as big compared to other countries. The lack of united voice by the whole cooperative movement and the lack of historical evolution could be the factors that lead to this consequence. The cooperatives must take initiatives to break into the present monopolist-monopsonist system. It must coordinate its efforts with those government agencies, to concentrate on one or two specifically designated area or sector with a few limited objectives. And finally, the harmony of action and positive mindset from the highest apex level to the lowest primary cooperative are very much needed to expand the cooperative movement nationwide.